Answer:
A' (-4, - 7), B' (-5, -4), C' (-4, -3), D' (-3, -4)
Explanation:
When rotating about the origin at an angle of 90° in the counterclockwise direction, the given values of (x, y) are interchanged with y also taking a negative sign. That is ;
(x, y) - - - -> (-y, x)
Therefore, in the question above ;
Translation = (x-2, y+3)
A =(-5, 1) = (-5 - 2, 1 + 3) = (-7, 4) - - -> A' = (-4, - 7)
B =(-2, 2) = (-2 - 2, 2 + 3) =(-4, 5) - - -> B' = (-5, -4)
C =(-1, 1) = (-1 - 2, 1 + 3) = (-3, 4) - - -> C' = (-4, -3)
D =(-2, 0) = (-2 - 2, 0+3) =(-4, 3) - - -> D' = (-3, -4)